PEMBANGUNAN SISTEM DASHBOARD HUMAN RESOURCES UNTUK PEMANTAUAN KINERJA KARYAWAN PT X BERBASIS WEB - Putri, Ilafi Firsta; Nuryani, Maudy; Sari, Yustiana (Universitas Komputer Indonesia, 2019)
PT X is one of the largest mining companies in Indonesia. As a company that continues to grow, the Department of Human Resources (HR) at the company be able to provide all employee information and can support employee performance. HR still uses Microsoft Excel as the presentation of visual information in the performance management system. This will be a problem in the information and evaluation process associated with employees. To help the process of reengineering the system, the company requires a good computerized and integrated system, making information can be given well to all users and the company gets accurate information. In improving the rescue process, data and information are needed from all parts of the department. The author makes a web-based dashboard system in presenting information and for promoting employee performance. This dashboard is used by the Human Resources Department (HRD). The dashboard system is built using the bootstrap framework. With the dashboard system, web-based human resources will make it easier to provide information about employees. Key words : Dashboard, Human Resources, Monitoring